Integrating Mechanisms of Exacerbated Atrophy and Other Adverse Skeletal Muscle Impact in COPD - Taivassalo, Tanja; Hepple, Russell T. (Frontiers in Physiology, 2022)
The normal decline in skeletal muscle mass that occurs with aging is exacerbated in patients with chronic obstructive pulmonary disease (COPD) and contributes to poor health outcomes, including a greater risk of death. There has been controversy about the causes of this exacerbated muscle atrophy, with considerable debate about the degree to which it reflects the very sedentary nature of COPD patients versus being precipitated by various aspects of the COPD pathophysiology. Consistent with the latter view, recent evidence suggests that exacerbated aging muscle loss with COPD is likely initiated by decades of smoking-induced stress on the neuromuscular junction that predisposes patients to premature failure of muscle reinnervation capacity, accompanied by various alterations in mitochondrial function. Superimposed upon this are various aspects of COPD pathophysiology, such as hypercapnia and hypoxia, that can also contribute to muscle atrophy. This review will summarize the available knowledge concerning the mechanisms contributing to exacerbated aging muscle affect in COPD, consider the potential role of comorbidities using the specific example of chronic kidney disease, and identify emerging molecular mechanisms of muscle impairment, including mitochondrial permeability transition as a mechanism of muscle atrophy, and chronic activation of the aryl hydrocarbon receptor in driving COPD muscle pathophysiology.